Gender, sexuality, and young adults in Malaysian Universities: A phenomenological study and implications for sexuality education and sexual health / Zahra Fazli Khalaf - Khalaf, Zahra Fazli (2014)

(untitled)
Gender and sexuality are central aspects of human identity, and play an essential role in every aspect of people’s lives. Perceptions of gender and sexuality strongly affect the health status and general wellbeing of individuals. Although the importance of gender and sexuality has been widely discussed in the health literature, little is known about the meanings that people give to these concepts at different social classes and life stages. Young adulthood is a distinct period of development “characterized by identity explorations.” The concepts of gender and sexuality are two important areas of identity exploration that influence the young adults’ identity stabilization and leading them to embrace the adult roles. In addition, young adults who pursue higher education and delay in marriage, experience a prolonged transition to adulthood due to social and economic changes that might result in different issues and challenges with regard to the concepts of gender and sexuality. The international contexts of universities in Malaysia provided opportunities for intermingling of different cultures and citizens that might result in new experiences and challenges. Iranian students form the highest number of university students in Malaysia. The purpose of this qualitative study was to explore the lived experiences and perceptions of gender and sexuality among young adult Malaysian and Iranian university students in Malaysia in order to capture the common experiences, and joint issues and challenges among this diverse group. I adopted a Transcendental Phenomenology to explore the lived experiences of gender and sexuality among the heterosexual male and female young adults (20-30 years old) involving 22 Malaysian and Iranian university students. The Transcendental phenomenology methodology led to illustration of the essence of the experience common to the whole group. iv Findings illustrated the stereotypical and androcentric views of gender and sexuality. Concept of gender was associated with physical appearance, gender behaviors, gender roles, social positions and sexual abilities. Concept of sexuality was perceived in relation to pleasure and physical enjoyment, emotional attachment, trust and commitment, responsibility, and women’s dignity and social honor. Perceptions of gender and sexuality was affected by different factors in the social and environmental structures. The university context led to the experience of positive perceptions of gender, and was understood as an influential factor in achieving gender equality. In addition, the international context of the universities provided opportunities for the development of trans-national non-committal sexual relationships. The participants faced several issues and challenges in experiencing their gender and sexuality, and expressed their needs for knowledge, and suggested some areas of education to stakeholders. The substantive theoretical model emerged from this research provides a framework for the understanding of the lived experiences and faced issues of gender and sexuality among this diverse group of young adults. The model can draw on a practical framework for empowerment of university students to meet the issues of gender and sexuality in a healthier way. The study confirmed the quest for a comprehensive sexuality education at university level as well as educational programs for improving personal growth and interpersonal relationship skills, and counseling services for enhancing academic achievements and decision-making skills for future social life.